Relationship of musculoskeletal pain and well-being at work - Does pain matter? - Kirsi Malmberg-Ceder; Maija Haanpaa; Päivi E. Korhonen; Hannu Kautiainen; Seppo Soinila (ELSEVIER SCIENCE BV, 2022)
Background and aims: Musculoskeletal pain is a common symptom and many people even with chronic pain continue to work. The aim of our study is to analyze how musculoskeletal pain affects work wellbeing by comparing work engagement in employees with or without pain, and how pain-related risk of disability is associated with work engagement. In a separate analysis, we also studied, how psychosocial factors are related to work engagement.Methods: This is a cross-sectional study of Finnish female employees of the city of Pori, Finland (PORi To Aid Against Threats (PORTAAT) study). Data was collected by trained study nurses and self-administrated questionnaires. Work well-being was measured by work engagement using Utrecht Work Engagement Scale (UWES-9) questionnaire and the burden of pain was measured by using the short version of Orebro Musculoskeletal Pain Screening Questionnaire (OMPSQ). Study population was divided into four groups: those without pain and the groups with low ( I), medium (II) or high (III) OMPSQ score, reflecting increasing risk of long term disability due to musculoskeletal pain. The study nurse assessed psychosocial risk factors using defined core questions.Results: We evaluated 702 female employees, 601 (86%) had suffered from musculoskeletal pain over the past 12 months, whereas 101 (14%) reported no pain at all. Pain was chronic (duration at least 3 months) in 465/601 (77%) subjects. Subjects with musculoskeletal pain were older, had higher BMI and were on sick leave more often than subjects without pain. Of the psychosocial risk factors, depression, type D personality, anxiety and hostility were significantly more common among subjects with musculoskeletal pain. Hypertension and the use of non-steroidal anti-inflammatory drugs were significantly more frequent in the musculoskeletal pain group. Quality of sleep and working capability were significantly better among persons without pain. Average weekly working hours were slightly higher among those with musculoskeletal pain.In crude analysis, work engagement (UWES-9) was similar in women without pain and those with musculoskeletal pain (4.96 vs. 4.79; p = 0.091). After adjustment for age, education years, BMI, working hours and financial satisfaction, the difference between the groups became statistically significant (p = 0.036). Still, there was no difference between the groups of no-pain and low burden of pain (p = 0.21, after adjustment). Work engagement was significantly lower in the groups of medium (p = 0.024, after adjusted) and high(p < 0.001, after adjustment) burden of pain. Linearity across the Linton tertiles was significant (p < 0.001). In univariate and multivariate ordered logistic regression analyses relating study variables to the work engagement musculoskeletal pain per se did not enter in the model to explain work engagement. Work and family stress, type D personality and duration of sick leave due to pain reduced work engagement, whereas financial satisfaction, moderate and high leisure time physical activity and higher BMI improved it.Conclusions: Among women with musculoskeletal pain psychosocial and lifestyle factors significantly correlate with work engagement, while the pain itself does not. (C) 2016 Scandinavian Association for the Study of Pain. Published by Elsevier B.V. All rights reserved .